Metformin: A Bridge between Diabetes and Prostate Cancer - Zingales, Veronica; Distefano, Alfio; Raffaele, Marco; Zanghi, Antonio; Barbagallo, Ignazio; Vanella, Luca (Frontiers in Oncology, 2017)
Prostate cancer has become the most frequent type of cancer in men. Recent data suggest that diabetic patients taking metformin have a lower incidence of certain cancer, including prostate cancer. Metformin is the most common drug used in type II diabetes mellitus; its use has been shown to lower the incidence of several cancer, although there are ambiguous data about the anti-cancer activity of metformin. A large number of studies examined the potential antineoplastic mechanism of metformin although it is not still completely understood. This review summarizes the literature concerning the effects of metformin on prostate cancer cells, highlighting its numerous mechanisms of action through which it can act. We will analyse the possible causes of the discordances regarding the impact of metformin on risk of prostate cancer; we will discuss the latest findings in this field, suggesting that metformin may have a future role in the management of prostate cancer both as monotherapy and in combination with other drugs.